Quality of life of dialysis patients during the COVID-19 pandemic (Research, Society and Development, 2023)
Objective: To elucidate the effects of the COVID-19 pandemic on the quality of life of hemodialysis patients at Hospital do Rim de Guanambi. Methodology: Field research was carried out, with a quantitative approach and descriptive analysis. 47 patients undergoing renal replacement therapy at the Hospital do Rim de Guanambi - Bahia participated in the research. To assess quality of life, a sociodemographic form and the World Health Organization Quality of Life-Bref (WHOQOL-bref) were used. Results and Discussion: There was a prevalence of male participants, in addition to a greater concentration in the age group from 18 to 59 years old, with the majority suffering from Systemic Arterial Hypertension. Regarding quality of life scores, the best results were in the psychological and social relationships domains, followed by fair results in the environment domain and worse results in the physical domain. Conclusion: In general, the pandemic period did not negatively impact the quality of life of dialysis patients at Hospital do Rim de Guanambi-BA, as QoL is closely related to the perception they have of themselves.